Understanding molecular interaction between sulfadoxine and human serum albumin through spectroscopic and molecular docking methods / Jaslene Anne Francis - Jaslene Anne , Francis (2021)
The main aim of this study was to characterize the molecular interaction between sulfadoxine (SDN) and the major transport protein in the blood plasma, human serum albumin (HSA) using fluorescence, absorption, circular dichroism and voltammetric techniques along with computational methods. SDN-induced changes in the fluorescence intensity of HSA hinted the complex formation between SDN and HSA. Both values of the bimolecular quenching rate constant and UV-Vis absorption spectral results characterized the quenching of HSA fluorescence as static quenching. Analysis of the quenching results showed a moderate binding affinity (Ka = 3.39×104 M‒1 at 300 K) between SDN and HSA. Thermodynamic data (ΔS = + 104.42 J mol–1 K–1, ΔH = + 5.25 kJ mol–1) suggested participation of hydrophobic interactions as the main binding force in the complex formation. Secondary and tertiary structural changes along with microenvironmental perturbation around protein fluorophores were also noticed upon SDN binding. The voltammetric spectral analysis further supported the complex formation between HSA and SDN. Competitive ligand displacement results, as well as computational analysis, revealed binding of SDN to Sudlow’s Site I, located in subdomain IIA of HSA.